Preparation and characterization of alkyd coating with self-healing ability / Nornadila Mohd Saman - Nornadila , Mohd Saman (2019)
Apart from decorative purposes, coatings have also been applied to metal surface to inhibit corrosion by protecting the substrate from environmental exposure. This work focuses on the use of UV-curable palm oil-based alkyd for surface coating application. This type of coating is a form of environmentally friendly coating that involves low, if any, emission of volatile organic compounds (VOCs) during curing. Nonetheless, UV-cured alkyd coating is just similar to any other coatings, where it is vulnerable to damages such as formation of microcracks during its service. By introducing self-healing properties into the alkyd coating, it can avoid further catastrophic failure and prolong the lifespan of the coating and its substrate. One of the objectives of this study is to introduce self-healing ability to the alkyd coating. Self-healing alkyd coating consists of microcapsules containing healing agent, implanted into alkyd coating matrix. Alkyd was synthesized as a binder in this coating mixture while methyl methacrylate (MMA) serves as reactive diluents and benzophenone as UV-photoinitiator. Diglycidyl ether bisphenol-A based epoxy (EPON828) and pentaerythritol tetrakis (3-mercaptopropionate) (PETMP) were chosen as the healing agents and microencapsulated by in situ polymerization. Self-healing process of the coating took 10 minutes after the coating was intentionally scratched. The efficacy of the self-healing ability of the coating was investigated using high powered microscope and potentiodynamic polarization. The coating showed excellent corrosion resistance and recorded good film properties.